Peran Teknologi Dalam Perkembangan Pendidikan Islam Abad 21 Di Era Society 5.0 - Shofiyah Assyifa, Habibah; Fitriyah, Ima (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2024)
The purpose of writing this article is to determine the role of technology in developing Islamic education in the 21st century so that it can improve the teaching and learning process to be more effective and efficient in learning Islamic education material. The writing in this research uses a library research method in the form of a literature study. Based on several studies from books, documents and literatures that have been conducted, educational technology is able to support effective learning activities, especially in Islamic Religious Education material. The existence of technology can provide great benefits in Islamic education. Based on several studies that have been conducted, it can be concluded that educational technology is able to support effective learning activities, especially in Islamic Religious Education material. The existence of technology can provide great benefits in Islamic education. By using technology wisely in Islamic religious education, it will be able to have a good impact, especially for millennials. Even though there are still many challenges that need to be faced in the use of technology, technology plays an important role in the development of Islamic religious education in the 21st century in Society Era 5.0.